Modos de apropriação do gênero debate regrado na escola: uma abordagem aplicada - SANTOS, Sandoval Nonato Gomes (Universidade Federal do Pará, 2019)
The genre debate has its own particular rules. This study describes and analyses the production process of the genre debate in the mother language teaching and learning context, in High School juniors groups of a public school in Belém (PA). The aim of the study is to understand how this genre, as a teaching object, assumes the role of discipline content, that is, its status in the Portuguese language class. Students' productions, specifically the roles they assume to perform in this genre, are focused on. This focus implies considering not only the ways in which students learn the genre, but also their perceptions about the tasks they are involved in achieving